Comparison of Intraperitoneal Instillation of Bupivacaine versus Tramadol for Post-operative Pain in Patients Undergoing Laparoscopic Cholecystectomy - Farhan Ali, Abdul Bary, Hamid Raza Laghari, Muhammad Zafar, Muhammad Akram, Sirajuddin, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cholecystectomy, the surgical removal of the gallbladder, is commonly performed via laparoscopic methods, which is widely regarded as the standard treatment for symptomatic cholelithiasis. Laparoscopic cholecystectomy is often done as day-case surgery due to its advantages, including reduced pain, shorter hospital stays, and a quicker return to daily activities. A key aspect of this procedure is intra-peritoneal instillation for pain management. Two commonly used agents for this are bupivacaine, a local anesthetic, and tramadol, an opioid pain medication. However, there is ongoing debate about which of these agents is more effective for post-operative pain control. Objective: This study aims to compare the efficacy of bupivacaine and tramadol in managing pain following laparoscopic cholecystectomy. Methodology: This randomized controlled trial was conducted at the department of General Surgery Pir abdul qadir shah jeelani institute of medical sciences, Gambat over a six-month period. A total of 100 patients were included, selected using a non-probability consecutive sampling technique. Informed consent was obtained from all participants. Patients were randomly assigned to two groups using the lottery method. One group (group T) received 100mg of intraperitoneal tramadol, while the other group (group B) received 0.25% bupivacaine. Pain levels were assessed 24 hours post-operatively using the Visual Analogue Scale (VAS). The data were analyzed using SPSS 17, with a t-test applied to compare mean pain scores between the two groups, considering a p-value of ≤0.05 as statistically significant. Results: The mean age of participants was 36.81±7.59 years, with 68% male and 32% female patients. In terms of body mass index (BMI), 30% of patients were of normal weight, 25% were overweight, and 45% were obese. The overall mean pain score was 5.39±1.61. The mean pain score in the bupivacaine group was 6.10±1.52, whereas in the tramadol group, it was 4.68±1.39. This difference was statistically significant with a p-value of 0.000. Conclusion: The results of this study indicate that tramadol is a more effective analgesic than bupivacaine for controlling post-operative pain in patients undergoing laparoscopic cholecystectomy. Keywords: Cholecystectomy, Tramadol, Bupivacaine, Pain, Intraperitoneal instillation.